Business model innovation and organisational mindfulness as determinants of corporate sustainability: an empirical study. (2017) - Vihari, Nitin Simha; Rao, M.K.
The aim of this paper is to study the influence of the determinants such as business model innovation (BMI) and organisational mindfulness (OM) on the corporate sustainability (CS) and organisational effectiveness (OE) with special reference to select pharmaceutical firms in India. The survey which was adopted and designed on five-point Likert scale was disseminated both via web-based and manual channels. Multivariate multiple regression analysis (MMRA) from the family of general linear model (GLM) is used to observe the explained variability of both the dependent variables by the independent variables individually. Key findings of the study underlines that an organisation which is highly sensitive to perception and depicts the flexibility in its behaviour by responding to diverse changing stimuli and those organisations who innovate by leveraging the internal resources would contribute to the enhancement of CS and OE. This study has implications for both practitioners and academicians.